Self-recovering mechanochromic luminescent material with aggregation-induced emission: Implication for pressure sensor. (August 2019) - Zhao, Ruixue; Zhao, Li; Zhang, Mengyao; Li, Zhongfeng; Liu, Yang; Han, Tianyu; Duan, Yuai; Gao, Kun
Abstract: In this work, we report the synthesis and emission behavior of a new compound, ( E )-butyl 4-(((2-hydroxynaphthalen-1-yl)methylene)amino)benzoate (BOMAB ). The molecular design includes twisted conformation and the incorporation of electron donor (D), acceptor (A) and a flexible alkyl chain. The compound shows both intramolecular charge transfer (ICT) character and aggregation-induced emission (AIE) nature. Furthermore, it exhibits mechanochromic luminescence: The solid powder gives strong emission but shows remarkable quenching with a bathochromic-shift after grinding, demonstrating high contrast. More importantly, the force-induced emission state can change back to the initial state without any treatment, showing self-recovery ability. Raising the temperature will accelerate the self-recovering process but partly quench the emission due to thermal motion of molecules. It takes 180 min for the ground sample to fully recover at 20 °C but only 18 min for that at 80 °C. As verified by crystallographic data, the phase transition is not a necessary condition for the mechanochromic nature of BOMAB . Such self-recovering mechanochromic luminescence can be attributed to the combined effect of conformational change and partly disordered packing. This makes BOMAB superior to other counterparts on account of its sensitivity and reusability. We developed a new type of pressure sensor using this material. In the quantitative mechanical test, the sensor shows a remarkable emission loss with the external pressure, and gives a linear relation with the pressure in lower range (0–73.2 N). The detection limit of the pressure sensor is 12.16 Mpa, showing high sensitivity. Graphical abstract: Image 1 Highlights: A luminescent material shows both AIE and mechanochromic properties. The mechanochromic luminescence exhibits self-recovering ability. A pressure sensor is developed based on this material, showing high sensitivity.